The use of recovery strategies by Spanish first division soccer teams: a cross-sectional survey - Altarriba-Bartes, A.; Peña, J.; Vicens-Bordas, J.; Casals, M.; Peirau, X.; Calleja-González, J. (The Physician and Sportsmedicine, 2021)
Objectives different active and passive post-exercise recovery techniques such as massage, foam rolling, stretching or ice baths among others, are used by elite athletes to promote effective physiological, physical, and mental restoration. However, limited research is available investigating the use of recovery strategies in professional soccer. As such, we aimed to explore and describe the use of strategies by professional teams throughout the season, describing competitive and preparatory phases.